ONE INDIAN GIRL: AN EXEMPLIFICATION OF BE WHO YOU ARE AND SAY WHAT YOU FEEL - Anand, Neha; Dhingra, Manish; Gola, Kamal Kumar; Rathore, Rahul (International Journal of Psychosocial Rehabilitation, 2020)
Bhagat, as a writer, needs no introduction. The well-liked fiction novelist holds the credential of being The Best Seller right from his debut novella Five Point Someone to his newborn publication One Indian Girl. In the literary cosmos he has left his mark successfully.His literary works leave no stone unturned to explore human relationships on the ground of societal, political and economic standards. This is, unquestionably, one of the reasons why he has grabbed hold of across-the-board critical acclaim in addition to a just about equal share of blame. His latest novel One Indian Girl (2016) is no exception to this.Whereas some reviewers are admiring the novel as a psychological conquest, at the same timemany are there who possess the mind to put the author on blame for vilifying Indian womanhood. The present study is an attempt to examine the feminist element inview of the plot, characterization and overall ambience depicted in the novel.This present paper focuses on feminism and the rapidly changing shadesof female thought process who are emulous and tech savvy. The protagonist, Radhika Mehta represents the girls of modern India who even though pressure from society, often vigorously execute what they prefer without raging an external battle, without giving a single ray of thought to what society anticipates or considers is apt for a woman of the time